Design and Measurement of Planar Monopole Antennas for Multi-Band Wireless Applications. Issue 2 (4th March 2017) - Shah, S. A. A.; Khan, M. F.; Ullah, S.; Basir, A.; Ali, U.; Naeem, U.
ABSTRACT: This paper presents the design of compact and low profile multi-band/reconfigurable planar monopole antennas using a 1.6 mm-thicker FR4 substrate and a truncated ground-plane. One of the proposed structures (Antenna2) is reconfigured using optical switch. The proposed antennas can operate in single- and dual-band modes depending on the STATE of the switch. Antenna1 operates in dual-band mode (Wi-Fi @ 2.45 GHz and WLAN @ 5.4 GHz). Antenna2 gives two distinct dual-band modes depending on the state of the switch, i.e. (Wi-Fi @ 2.45 GHz and WLAN @ 5.13 GHz) and (WiMAX @ 3.49 GHz and WLAN @ 5.81 GHz), when the switch is ON and OFF, respectively. The proposed structures achieve bandwidths ranging from 11% to 36% at respective centred frequencies. The antennas are designed with input impedance in the range of 45–53 Ω having VSWR < 1.27 for operating frequency bands. Gain values from 1.6 to 3 dBi and radiating efficiencies from 76.4% to 92% are attained at required operating bands. The proposed antennas are light-weight, low-profile, and easily fabricated. Therefore, they are potential candidates for use in portable and intelligent mobile phones, laptops, PDAs, and iPads as well as for military, rescue, safety, and medical applications. Using a numerical Finite Integration Technique employed in Computer Simulation Technology Microwave Studio, the antennas far-field, scattering, and gain parameters are evaluated. The antennas are fabricated and a good agreement between the measured and simulated results is observed.